2022
DOI: 10.3389/fpls.2021.794488
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Selection for Seed Ability to Germinate at Extreme Temperatures in Perennial Ryegrass (Lolium perenne L.)

Abstract: Various adaptive mechanisms can ensure that seedlings are established at the most favourable time and place. These mechanisms include seed dormancy i.e., incapacity to germinate in any environment without a specific environmental trigger and inhibition i.e., incapacity to germinate in an unfavourable environment (water availability, temperature: thermoinhibition and light). The objective of this research was to study in the temperate range for germination of forage and turf grass species perennial ryegrass, if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Germination is a complex biological process influenced by genetic and environmental factors including temperature (Shafii and Price, 2001). However, the genetic diversity of response to temperature during seed germination of pasture species has received little attention (Volaire et al, 2016;Ahmed et al, 2019;Ghaleb et al, 2021Ghaleb et al, , 2022. A similar situation is observed for the study of initial heterotrophic growth in general (Escobar-Gutiérrez et al, 1998a,b) and of pastures in particular (Ahmed, 2015).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Germination is a complex biological process influenced by genetic and environmental factors including temperature (Shafii and Price, 2001). However, the genetic diversity of response to temperature during seed germination of pasture species has received little attention (Volaire et al, 2016;Ahmed et al, 2019;Ghaleb et al, 2021Ghaleb et al, , 2022. A similar situation is observed for the study of initial heterotrophic growth in general (Escobar-Gutiérrez et al, 1998a,b) and of pastures in particular (Ahmed, 2015).…”
Section: Discussionmentioning
confidence: 89%
“…The results presented here reveal, for the first time, high genetic variability within L. perenne germplasm for the response to temperature in the initial life phases. We have recently shown that the response of germination to temperature is at least partially controlled genetically (Ghaleb et al, 2022). Thus, the newly discovered genetic variability should serve breeders to create perennial ryegrass varieties for the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of chemical and biochemical reactions, as well as the rates of cell growth and plant functioning, all depend on the temperature [6,7]. The relationship between seed germination and temperature has been extensively studied [2,8], and several mathematical models have been proposed to describe such a relationship that can be expressed in terms of the cardinal temperatures [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of intraspecific genetic diversity is crucial for its conservation [5] and utilization [12]. However, as for many other species, published knowledge is scarce concerning the intraspecific variability of tall fescue in response to climate factors, particularly to temperature during germination and early growth [7].…”
Section: Introductionmentioning
confidence: 99%